PENGAWASAN PEMANFAATAN DAN PENGGUNAAN BAGIAN - BAGIAN JALAN OLEH DINAS BINA MARGA KOTA PEKANBARU - Della Hardi; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Oversight is one of the processes to establish what work has been carried out, vote and correct it if necessary with the intention that the implementation of the work in accordance with its intended purpose. Supervision is done by Dinas Bina Marga Kota Pekanbaru has not felt the maximum because there are still many communities that do not kno function street poles and cause distortions road function. The purpose of this research is how to supervise the utilization and use of parts of the road by Dinas Bina Marga Pekanbaru City and to determine the factors that influence the use of surveillance and use parts of the road by Dinas Bina Marga Kota Pekanbaru.The concept of the theory used by the authors is the Management and Supervision. Researchers used descriptive qualitative research studies. In collecting the data, the authors use the technique of interviewing and observation. The authors use informants as sources of information and techniques triagulasi as a source of data validity.Results of this study indicate that the use of surveillance and the use of parts of the road by Dinas Bina Marga Kota Pekanbaru still not up, proved there are deviations that are found in Parts of the city of Pekanbaru. Factors that influence the use of surveillance and the use of parts of the road by Dinas Bina Marga Kota Pekanbaru is community participation, budget systems is not maximized and infrastructure in conducting surveillance.Keywords: Controling, Utilization, Use of Parts of the Road